Multiple brain abscess in systemic lupus erythematosus patients - Ismy, Jufitriani; Anidar; Sari, Desi Purnama (Journal of International Surgery and Clinical Medicine, 2024)
Introduction: Because SLE patients receive immunosuppressive and glucocorticoid medication, they are more susceptible to opportunistic infections. Multiple brain abscesses are an extremely uncommon side effect of systemic lupus erythematosus (SLE). Case description: The purpose of this case study is to raise awareness of the 14-year-old girl who reported experiencing weakness in her limbs. A year ago, she received a diagnosis of systemic lupus erythematosus. Upon physical examination, nervus VII central paresis was discovered; the lower extremities' muscular strength was 3333/2222 and the upper extremities' 3333/2222. A head CT scan revealed findings that were consistent with lupus cerebritis. Multiple ring lesions with extensive edoema were detected by magnetic resonance imaging, raising the possibility of multiple brain abscesses. For six weeks, the patient had intravenous metronidazole and ceftriaxone. The patient was allowed to go home with instructions to keep taking corticosteroids and mycophenolic acid as well as to schedule routine outpatient appointments. This case study aims to raise awareness about the 14-year-old girl who reported experiencing weakness in her limbs. Her condition was identified by specialists as systemic lupus erythematosus a year ago. Upon physical examination, nervus VII central paresis was discovered; the lower extremities' muscular strength was 3333/2222 and the upper extremities' 3333/2222. A head CT scan revealed findings that were consistent with lupus cerebritis. Multiple ring lesions with extensive edoema were detected by magnetic resonance imaging, raising the possibility of multiple brain abscesses. For six weeks, the patient received metronidazole and ceftriaxone intravenously. We sent the patient home with instructions to keep taking mycophenolic acid and corticosteroids and to make routine outpatient appointments. This case study aims to raise awareness about the 14-year-old girl who reported experiencing weakness in her limbs. Her condition was identified by specialists as systemic lupus erythematosus a year ago. Upon physical examination, nervus VII central paresis was discovered; the lower extremities' muscular strength was 3333/2222 and the upper extremities' 3333/2222. A head CT scan revealed findings that were consistent with lupus cerebritis. Multiple ring lesions with extensive edoema were detected by magnetic resonance imaging, raising the possibility of multiple brain abscesses. For six weeks, the patient received metronidazole and ceftriaxone intravenously. We sent the patient home with instructions to keep taking mycophenolic acid and corticosteroids and to make routine outpatient visits. Conclusion: It is critical to being aware that individuals with impaired immune systems should always be suspected of having an opportunistic central nervous system infection when they experience new neurologic symptoms. A brain abscess is a chronic infection of the central nervous system that can arise from a number of risk factors and infection sources. A brain abscess is one of the uncommon side effects of SLE.